TINJAUAN KRIMINOLOGI TERHADAP TINDAK PIDANA KEKERASAN ANTAR WARGA EKS TIMOR-TIMUR DAN WARGA LOKAL SECARA BERULANG-ULANG DI KABUPATEN KUPANG - Pakh, Wian Krista; Leo, Rudepel Petrus; Amalo, Heryanto (Petitum Law Journal, 2025)
Recurrent violent conflicts between former East Timorese refugees and local communities in Kupang Regency (2005-2018) were caused by competition over economic resources, negative views, and identity issues after the 1999 referendum. This legal research investigates the causes and ways of resolving the conflict with a focus on Tanah Merah Village, Central Kupang—an area chosen because it has a long history of conflict and structural injustices that reflect the overall dynamics of the area. The methods used include structured interviews with stakeholders (sources: local residents, former refugees, traditional leaders, and the police) and secondary data analysis. The main findings highlight the causal factors that drive the conflict: high unemployment (especially among young people), limited legal insight, extortion practices, land disputes, and alcohol consumption that can trigger anarchic actions. Successful intervention measures include: (1) early prevention through security posts and legal education (reducing violence by 25% by 2022), (2) community-based mediation (with an effectiveness rate of 40% according to ELSAM 2021), and (3) strict enforcement of the law (Articles 170-182 of the Criminal Code). Policy recommendations include: regulating the sale of alcoholic beverages within a certain radius in conflict-prone areas, integrated job training programs for unemployed youth, and accelerating the customary land certification process to break the cycle of structural violence.